Agro-pastoralists use participatory video making to reflect on their food environment in Turkana, Kenya - Jordan, Irmgard; Natukunda, A.; Waswa, L.M.; Termote, Celine; Keding, G.B. (2024)
Food Environment: • Where people select, acquire, prepare and consume food.